Resenha crítica: leitura e desenvolvimento da argumentação no 9º ano do ensino fundamental - França, Lucineide Pires da Silva (2022)
The textual/discursive genre review is one of the most developed in the academic sphere, especially regarding the practice of assessing reading for argumentative development. Of this genre, several skills and competencies of the students are worked and experienced, promoting the development of reading, argumentative competence and explanation of ideas. In this sense, the general objective of this research is to demonstrate the importance of reading the textual/discursive genre critical review for the development of the argumentative competence of elementary school students final years based on the construction of a didactic sequence that functions as a pedagogical proposal in this favor. Therefore, it presents as specific objectives: to propose a didactic sequence, focused on the 9th year of elementary school, which addresses the textual/discursive genre critical review based on the skills and competencies of the BNCC; to present the contributions of linguistic theories that deal with argumentation through the clipping of the phenomenon of argumentative operators; discuss the results of the application of the didactic sequence elaborated for a 9th grade class, from the Municipal School Ermelinda de Lucena Barbosa, aiming to understand the importance of reading the genre critical review in this school context. Methodologically, the suggestion for the development of a didactic sequence that was applied in a 9th grade class is detailed. This dissertation is based on theoretical principles that make references to textual linguistics and reading practices for the development of argumentation. These authors make reflections and questions about the theme in the classroom and highlight the favoring of some instruments in the conduction of the teaching and learning process and development of language skills. Among them are: Bakhtin (1999), when presenting language as a social, historical and ideological phenomenon; Kleiman (2002) and (2004), addressing the importance and reading strategies in linguistic development and "The Reading Approaches of Applied Linguistics"; Martins (1974), in his work "What is reading"; Koch (1992) and (2000) when addressing the aspects of argumentation in language and also (2011), by elective operators; Marcuschi (2008), by evidencing the analysis of genres and textual comprehension. In this perspective, as the guide of the defense of reading teaching, information contained in some official documents such as BNCC (2017) and PCN (1998) was considered. We also highlight the contributions of argumentative theories in the process of development of argumentativeness, because the uses of analytical strategies in the various textual/discursive possibilities will allow criticality, reflexivity and creativity in linguistic uses. Therefore, this research has the perspective that the reading of the textual/discursive genre critical review contributes to the development of argumentative skills and the achievement of fundamental linguistic-discursive skills for integral training of learners by enabling critical analysis and positioning regarding discourses inserted in other textual/discursive genres.